Khopa (classic bun) hairstyle of Koli women - Mumbai Archive Project Team (Jio Institute, 2024)
The khopa (classic bun) is one of the most traditional hairstyles for Koli women. It involves gathering the hair at the back of the head and twisting it into a neat bun. As is customary in the region, they adorn their hair buns with scented and colourful flowers.